2018
DOI: 10.1186/s13068-018-1331-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome analyses of oleaginous Botryococcus braunii race A reveal significant differences in gene expression upon cobalt enrichment

Abstract: BackgroundBotryococcus braunii is known for its high hydrocarbon content, thus making it a strong candidate feedstock for biofuel production. Previous study has revealed that a high cobalt concentration can promote hydrocarbon synthesis and it has little effect on growth of B. braunii cells. However, mechanisms beyond the cobalt enrichment remain unknown. This study seeks to explore the physiological and transcriptional response and the metabolic pathways involved in cobalt-induced hydrocarbon synthesis in alg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 47 publications
(81 reference statements)
0
4
0
Order By: Relevance
“…Excess cobalt can be harmful to cells, resulting in diminished growth and lipids accumulation. Furthermore, the response of microalgae to cobalt stress varies by strain, with certain strains showing no substantial increase in hydrocarbon or lipid synthesis under cobalt stress conditions [66]. While cobalt stress can accelerate the synthesis of hydrocarbons and lipids in specific microalgae strains, cobalt levels must be carefully In this study, we investigated the effect of different concentrations of cobalt nitrate (0.49, 1, 5, 10, and 50 mg/L) on the production of biomass, lipids, and hydrocarbons by B. braunii cultivated in BBM 3N within a mini-photobioreactor.…”
Section: Effect Of Cobalt Stress On the Production Of Hydrocarbons An...mentioning
confidence: 99%
See 3 more Smart Citations
“…Excess cobalt can be harmful to cells, resulting in diminished growth and lipids accumulation. Furthermore, the response of microalgae to cobalt stress varies by strain, with certain strains showing no substantial increase in hydrocarbon or lipid synthesis under cobalt stress conditions [66]. While cobalt stress can accelerate the synthesis of hydrocarbons and lipids in specific microalgae strains, cobalt levels must be carefully In this study, we investigated the effect of different concentrations of cobalt nitrate (0.49, 1, 5, 10, and 50 mg/L) on the production of biomass, lipids, and hydrocarbons by B. braunii cultivated in BBM 3N within a mini-photobioreactor.…”
Section: Effect Of Cobalt Stress On the Production Of Hydrocarbons An...mentioning
confidence: 99%
“…The transcriptome of B. braunii over four time points during the cobalt treatment, as proposed by Cheng et al, showed that the most strongly expressed genes under high concentration were those related to fatty acid biosynthesis and metabolism, as well as oxidative phosphorylation; conversely, the most downregulated genes were related to carbohydrate metabolism, photosynthesis, and amino acid metabolism. The global gene transcript patterns indicated that different phenotypes under cobalt enrichment are likely caused by different expression dynamics [66].…”
Section: Effect Of Cobalt Stress On the Production Of Hydrocarbons An...mentioning
confidence: 99%
See 2 more Smart Citations